A Praline‐Like Flexible Interlayer with Highly Mounted Polysulfide Anchors for Lithium–Sulfur Batteries. Issue 40 (21st August 2017) - Zhao, Teng; Ye, Yusheng; Lao, Cheng‐Yen; Divitini, Giorgio; Coxon, Paul R.; Peng, Xiaoyu; He, Xiong; Kim, Hyun‐Kyung; Xi, Kai; Ducati, Caterina; Chen, Renjie; Liu, Yingjun; et al.
Abstract: The development of lithium–sulfur (Li–S) batteries is dogged by the rapid capacity decay arising from polysulfide dissolution and diffusion in organic electrolytes. To solve this critical issue, a praline‐like flexible interlayer consisting of high‐loading titanium oxide (TiO2 ) nanoparticles and relatively long carbon nanofibers is fabricated. TiO2 nanoparticles with a size gradient occupy both the external and internal of carbon fiber and serve as anchors that allow the chemical adsorption of polysulfides through a conductive nanoarchitecture. The porous conductive carbon backbone helps in the physical absorption of polysulfides and provides redox reaction sites to allow the polysulfides to be reused. More importantly, it offers enough mechanical strength to support a high load TiO2 nanoparticle (79 wt%) that maximizes their chemical role, and can accommodate the large volume changes. Significant enhancement in cycle stability and rate capability is achieved for a readily available sulfur/multi‐walled carbon nanotube composite cathode simply by incorporating this hierarchically nanostructured interlayer. The design and synthesis of interlayers by in situ integration of metal oxides and carbon fibers via a simple route offers the potential to advance Li–S batteries for practical applications in the future. Abstract : A praline‐like structural morphology of flexible interlayer, which consists of high‐loading titanium oxide nanoparticles and relatively long carbon fibers, is reported for the first time to significantly improve the cycle life and rate performance of lithium–sulfur batteries by chemical adsorption of polysulfides through a conductive nanoarchitecture.